Effects of Arachidonic Acid Supplementation on Acute Anabolic Signaling and Chronic Functional Performance and Body Composition Adaptations. - Eduardo O De Souza; Ryan P Lowery; Jacob M Wilson; Matthew H Sharp; Christopher Brooks Mobley; Carlton D Fox; Hector L Lopez; Kevin A Shields; Jacob T Rauch; James C Healy; Richard M Thompson; Jacob A Ormes; et al. (PLoS ONE)
Background The primary purpose of this investigation was to examine the effects of arachidonic acid (ARA) supplementation on functional performance and body composition in trained males. In addition, we performed a secondary study looking at molecular responses of ARA supplementation following an acute exercise bout in rodents. Methods Thirty strength-trained males (age: 20.4 ± 2.1 yrs) were randomly divided into two groups: ARA or placebo (i.e. CTL). Then, both groups underwent an 8-week, 3-day per week, non-periodized training protocol. Quadriceps muscle thickness, whole-body composition scan (DEXA), muscle strength, and power were assessed at baseline and post-test. In the rodent model, male Wistar rats (~250 g, ~8 weeks old) were pre-fed with either ARA or water (CTL) for 8 days and were fed the final dose of ARA prior to being acutely strength trained via electrical stimulation on unilateral plantar flexions. A mixed muscle sample was removed from the exercised and non-exercised leg 3 hours post-exercise. Results Lean body mass (2.9%, p<0.0005), upper-body strength (8.7%, p<0.0001), and peak power (12.7%, p<0.0001) increased only in the ARA group. For the animal trial, GSK-β (Ser9) phosphorylation (p<0.001) independent of exercise and AMPK phosphorylation after exercise (p-AMPK less in ARA, p = 0.041) were different in ARA-fed versus CTL rats. Conclusions Our findings suggest that ARA supplementation can positively augment strength-training induced adaptations in resistance-trained males. However, chronic studies at the molecular level are required to further elucidate how ARA combined with strength training affect muscle adaptation.